P833 HSV-2 serostatus and HPV incidence, persistence, and precancerous lesions in a cohort of HPV-vaccinated women living with HIV. (14th July 2019) - Mcclymont, Elisabeth; Coutlée, François; Lee, Marette; Albert, Arianne; Walmsley, Sharon; Lipsky, Nancy; Ogilvie, Gina; Tan, Darrell; Money, Deborah
Abstract : Background: In understanding HPV oncogenesis, several co-factors have been proposed including co-infection with HSV-2. We assessed the relationship between HSV-2 serostatus and HPV-related outcomes in a cohort of quadrivalent HPV-vaccinated women living with HIV (WLWH). Methods: In this multi-site study of immunogenicity and efficacy of the qHPV vaccine in WLWH, three doses of qHPV vaccine were offered. Visits were at months -3, 0, 2, 6, 12, 18, 24, and annually thereafter. Participants provided clinical data and cervico-vaginal swabs for HPV DNA detection (Linear array assay) at each visit; baseline serum was tested for HSV-2 type-specific serology (Focus EIA). We used non-parametric statistics to compare the HPV-related outcomes (including 37 high and low-risk HPV types) according to HSV-2 serostatus. Results: 151 women aged ≥16 provided baseline serum samples for HSV-2 testing. The predominant regions of origin were Canada (51%) and Africa (30%). At baseline, median age was 39 years (IQR: 34–45), median CD4 count was 500 cells/mm 3 (IQR: 382–692), and 70% had an HIV viral load <50 copies/mL. Baseline seroprevalence of HSV-2 was 76.2%, and median years of follow-up was similar for HSV-2 positive (6, IQR: 5.0–7.8) and negative (6, IQR: 5.2–7.9) participants. HSV-2 positivity was significantly associated with increased age. HSV-2 seropositive and seronegative participants had similar frequencies of HPV persistence (86/115 vs 27/36, p=1), clearance of incident HPV infections (88/115 vs 26/36, p=0.8), number of HPV types detected during the study (4.5 vs 5.7, p=0.1), HSIL cytology during the study (11/115 vs 2/36, p=0.7), and CIN2+ histology ever (15/115 vs 5/36, p=1). Results were similar in sensitivity analyses in which HSV-2 seropositivity was defined as an index value ≥3.5. Conclusion: HSV-2 seropositivity was common in this cohort of WLWH in Canada, but was not associated with multiple measures of HPV incidence, persistence, and precancerous lesions. Disclosure: No significant relationships.